A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae) - Volynkin, Anton V.; Titov, Sergey V.; Černila, Matjaž; Truuverk, Andro; Saldaitis, Aidas (Zootaxa, 2019)
A new species of the genus Victrix Staudinger, 1879, V. akbet Volynkin, Titov & Černila, sp. nov. is described from Kazakhstan. The new species belongs to the subgenus Poliobrya Hampson, 1908. A diagnostic comparison is made with V. frigidalis Varga & Ronkay, 1991, V. fabiani Varga & Ronkay, 1989 and V. umovii (Eversmann, 1846). The adults and male and female genitalia of the new and related species are illustrated.